STRATEGY FOR STRENGTHENING CHARACTER EDUCATION IN SCHOOLS THROUGH THE IMPLEMENTATION OF THE INDEPENDENT LEARNING CURRICULUM - Agus Subairi (CV. ADIBA AISHA AMIRA, 2025)
This research aims to examine various strategies for strengthening character education in schools through the implementation of the Independent Learning Curriculum. Character education is an urgent need amidst the challenges of globalization, technological advances, and moral degradation that occurs among students. The Merdeka Curriculum is presented as an educational policy that offers a more holistic, flexible and contextual learning approach, thus providing great opportunities for building student character. The method used in this research is a literature review (library research) by analyzing various sources such as scientific journal articles, academic books, government regulations, and previous research reports. Data analysis techniques were carried out through content analysis and thematic synthesis. The results of the study show that the character strengthening strategy in the Merdeka Curriculum can be carried out through several approaches, including implementing the Pancasila Student Profile Strengthening Project (P5), integrating character values in cross-disciplinary learning, implementing differentiated learning, and using authentic assessment that emphasizes processes and attitudes. Factors supporting the success of this strategy include teacher readiness, availability of resources and training, as well as parent and community support. On the other hand, lack of teacher understanding, limited facilities, and minimal parental involvement are obstacles that need to be overcome. This study concludes that strengthening character education through the Independent Curriculum requires synergy of all educational elements so that implementation can be effective and sustainable